Observation of a neutron spin resonance in the bilayered superconductor CsCa2Fe4As4F2. (3rd August 2020) - Adroja, D T; Blundell, S J; Lang, F; Luo, H; Wang, Z-C; Cao, G-H
Abstract: We report inelastic neutron scattering (INS) investigations on the bilayer Fe-based superconductor CsCa2 Fe4 As4 F2 above and below its superconducting transition temperature T c ≈ 28.9 K to investigate the presence of a neutron spin resonance. This compound crystallises in a body-centred tetragonal lattice containing asymmetric double layers of Fe2 As2 separated by insulating CaF2 layers and is known to be highly anisotropic. Our INS study clearly reveals the presence of a neutron spin resonance that exhibits higher intensity at lower momentum transfer ( Q ) at 5 K compared to 54 K, at an energy of 15 meV. The energy E R of the observed spin resonance is broadly consistent with the relationship E R = 4.9 k B T c, but is slightly enhanced compared to the values observed in other Fe-based superconductors. We discuss the nature of the electron pairing symmetry by comparing the value of E R with that deduced from the total superconducting gap value integrated over the Fermi surface.